Improving The Use of Design Thinking Methodology in Teaching English for Specific Purposes (ESP) (Eurasian Journal of Learning and Academic Teaching, 2023)
Current article focuses on the topic of improving the use of design thinking methodology in teaching English for Specific Purposes (ESP). Design thinking is an innovative problemsolving approach that emphasizes empathy, collaboration, and experimentation. This annotation aims to explore the potential benefits and challenges of integrating design thinking into ESP education and discuss strategies to enhance its effectiveness